Empowering Student Publications: A Novel Approach through Student-Driven Research - Itagi, Anupama R; Mallidu, Jayashree; Chandaragi, Pooja; Kallimani, Padmaja (Journal of Engineering Education Transformations, 2025)
To foster technological self-sufficiency in alignment with India’s “Make in India” program, it is imperative to introduce initiatives that stimulate critical thinking among Engineering students. While theoretical and practical knowledge are pivotal in shaping the quality of future engineers. However, hands-on experience through lab courses and a project remains a conventional approach. Nevertheless, an increase in the number of projects enhances the problem-solving capability. This can be further taken to the next level by introducing student-driven research as part of the Engineering curriculum. Within this context, student-driven research emerges as a dynamic avenue, presenting students with a distinctive chance to cultivate vital skills, expand their knowledge, and nurture their professional advancement. This paper introduces the concept of Research- focused teaching and student publication as interconnected elements that can cultivate a culture of inquiry, innovation, and scholarly development among engineers. By merging these elements, educational institutions can nurture a generation of engineers proficient in research capabilities, contributing to technological advancement. The authors propose a comprehensive strategy for amplifying student-driven research through projects ensuring quality work leading to paper publication in standard conferences. The proposed approach introduces a novel team formation strategy, discusses evaluation rubrics, and explores potential graduate attributes attainment.